The Ghost of Crises Past: A Reply to Mooi and Gill - Craig, Matthew T. (Zootaxa, 2011)
The conclusion one might draw from all this is that the criterion used to define homology – i.e., the criterion of common ancestry – is a theoretical construct. Like truth, we must approximate it as best we can, and we have no touchstone to tell whether we have found it.---Colin Patterson, 1988: 621